2017
DOI: 10.1074/jbc.r116.760884
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs (lncRNAs) and their transcriptional control of inflammatory responses

Abstract: Edited by George M. Carman Long non-coding RNAs (lncRNAs) have emerged as potential key regulators of the inflammatory response, particularly by modulating the transcriptional control of inflammatory genes. lncRNAs may act as an enhancer or suppressor to inflammatory transcription, function as scaffold molecules through interactions with RNA-binding proteins in chromatin remodeling complexes, and modulate dynamic and epigenetic control of inflammatory transcription in a gene-specific and time-dependent fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 70 publications
2
162
0
Order By: Relevance
“…From pathological perspective of AIS, inflammation serves as a critical part in the disease exacerbation, which not only directly affects inflammatory pathways (including nuclear factor kappa‐light‐chain‐enhancer of activated B cell (NF‐κB) and Toll‐like receptor (TLR) pathways) to damage vascular wall, then changes vascular structure and promotes atherosclerosis, thereby decreasing blood flowing and increasing risk of AIS, but also indirectly increases neurocyte death through inducing TNF‐dependent apoptosis or necrosis in ischemic conditions, thereby accelerating the tissue damage in relevant part of the brain, retina, or spinal cord and facilitating the progression of AIS . According to the previous studies, several lncRNAs act as enhancers of inflammatory responses in AIS by activating inflammation‐related pathways such as NF‐κB pathway, TRL pathway, and JAK/STAT pathway . For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF‐α level in AIS animal models .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From pathological perspective of AIS, inflammation serves as a critical part in the disease exacerbation, which not only directly affects inflammatory pathways (including nuclear factor kappa‐light‐chain‐enhancer of activated B cell (NF‐κB) and Toll‐like receptor (TLR) pathways) to damage vascular wall, then changes vascular structure and promotes atherosclerosis, thereby decreasing blood flowing and increasing risk of AIS, but also indirectly increases neurocyte death through inducing TNF‐dependent apoptosis or necrosis in ischemic conditions, thereby accelerating the tissue damage in relevant part of the brain, retina, or spinal cord and facilitating the progression of AIS . According to the previous studies, several lncRNAs act as enhancers of inflammatory responses in AIS by activating inflammation‐related pathways such as NF‐κB pathway, TRL pathway, and JAK/STAT pathway . For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF‐α level in AIS animal models .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we discovered that (a) lnc-ITSN1-2 was highly and JAK/STAT pathway. [19][20][21][22] For instance, increased lncRNA H19 expression is associated with impaired neurological function and increased TNF-α level in AIS animal models. 23 Antisense non-coding RNA in the cyclin-dependent kinase inhibitor 4 locus (ANRIL), an antisense lncRNA co-clustered with p15/CDKN2B-p16/CDKN2A-p14/ ARF, is overexpressed in cerebral infarction rat models and plays a pro-inflammatory role by activating NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are ncRNAs with critical biological roles and a length of more than 200 nucleotides . The mechanisms of lncRNAs remain unclear, but increasing number of in vitro and in vivo studies have shown that lncRNAs can be expressed in macrophage during its development and control some gene expression . However, a systematic review uncovered the interactions among lncRNAs expressed in macrophage is not available.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: nbazan@lsuhsc.edu. 2 The abbreviations used are: lncRNA, long non-coding RNA; lincRNA, long intergenic non-coding RNA; AhR, aryl hydrocarbon receptor; DHA, docosahexaenoic acid.…”
Section: Control Of Immune-mediated Pathology Via the Aryl Hydrocarbomentioning
confidence: 99%
“…Mathy and Chen (2) refer to the evolving role of long noncoding RNAs (lncRNAs) 2 as transcriptional regulators of the inflammatory response. A group of lncRNAs is induced as part of the response to inflammation and acts as an enhancer or a suppressor of inflammatory transcription, with members behaving as scaffolds with RNA-binding proteins in chromatinremodeling complexes.…”
Section: Lncrnas and Their Transcriptional Control Of Inflammatory Rementioning
confidence: 99%